Perlindungan Hukum Bagi Pembeli dalam Perjanjian Jual Beli Tanah yang Dibuat dengan Akta di Bawah Tangan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
In social practice, land sale and purchase transactions are still frequently conducted through private agreements, mainly driven by mutual trust between the parties, cost considerations, and the perception that such procedures are simpler and faster. From the perspective of civil law, such sale and purchase agreements remain valid and legally binding as long as they fulfill the legal requirements of a valid contract as stipulated in Article 1320 of the Indonesian Civil Code. However, within the national land law system, land sale and purchase agreements executed under private deeds cannot serve as a legal basis for the transfer of land rights because they are not made before a Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT) as required by statutory regulations. This divergence in legal regulation gives rise to legal uncertainty, particularly for buyers acting in good faith. On the one hand, the agreement creates rights and obligations under civil law; on the other hand, it fails to provide legal certainty over land rights due to its inability to be registered. This condition reflects a tension between the civil law regime and the land law regime, while also indicating the weak legal protection afforded to good-faith buyers. These issues constitute the basis and urgency of this research.